Web Programming Learning Application using CodeIgniter - Juanda Juanda; Barany Fachri; Rio Septian Hardinata (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
Website applications that can be done using a framework such as a CMS (Content Management System) as a solution to provide solutions in web management. One of the software that is currently popular in building this CMS is CodeIgniter